Social Networks and Personal Security - Patryk Błasik (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The emergence of the Internet caused a significant simplification of interpersonal communication all over the world. True, the communication became fast, cheap and convenient and for people, who by nature are social beings, it enabled easy bonding, maintaining relationships and strengthened the feeling of belonging to one group or another. Along with development of the Internet social networking portals emerged becoming a popular means of communication and entertainment specifically dedicated to young people. The paper outlines the most important advantages and disadvantages of social networks especially with respect to security.